2017
DOI: 10.1055/s-0037-1607325
|View full text |Cite
|
Sign up to set email alerts
|

Community-Acquired MRSA Pericarditis and Mediastinitis in a Previously Healthy Infant

Abstract: Invasive community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) infections disproportionately affect children, but there are few pediatric reports of pericarditis and mediastinitis caused by CA-MRSA in previously healthy children. Here we report a severe case of CA-MRSA pericarditis with extension to the mediastinum and carotid sheath in a previously healthy 8-month-old infant who was successfully treated with surgical interventions and with a combination of daptomycin and vancomycin. The rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…One of these cases was found in a 2018 case report from the Journal of Pediatric Intensive Care by Sanchez et al who described an 8-month-old infant presenting with a 10-day history of fever and cardiopulmonary distress and was successfully treated with a 2-week course of vancomycin, 5 days of daptomycin and 4 weeks of oral linezolid, while the other two cases were from an article by Lutmer et al in the Annals of American Thoracic Society Journal where the authors reported an 8-year old male and a 7-month old female who both presented with fever and cardiopulmonary distress both effectively treated with a combination of vancomycin, gentamicin and rifampin. 4,8 Similar to our patient, pericardial drainage was performed in all three cases, however, a 4-week course of vancomycin proved enough to effectively treat the infection in our case. Unique to our case, however, is the presence of tamponade physiology.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…One of these cases was found in a 2018 case report from the Journal of Pediatric Intensive Care by Sanchez et al who described an 8-month-old infant presenting with a 10-day history of fever and cardiopulmonary distress and was successfully treated with a 2-week course of vancomycin, 5 days of daptomycin and 4 weeks of oral linezolid, while the other two cases were from an article by Lutmer et al in the Annals of American Thoracic Society Journal where the authors reported an 8-year old male and a 7-month old female who both presented with fever and cardiopulmonary distress both effectively treated with a combination of vancomycin, gentamicin and rifampin. 4,8 Similar to our patient, pericardial drainage was performed in all three cases, however, a 4-week course of vancomycin proved enough to effectively treat the infection in our case. Unique to our case, however, is the presence of tamponade physiology.…”
Section: Discussionsupporting
confidence: 59%
“…[12][13][14] We suspect that our patient was already colonized with MRSA and it has gained access into the blood stream via microabrasions from the skin that may have healed and was therefore missed during the physical examination. 8 Confirmation of patient's MRSA carriage was not carried out.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pericarditis due to MRSA is a rare event, only a handful of cases (12 patients) have been reported in the literature (Table 1). [6][7][8][9][10][11][12][13][14][15] Our review of literature revealed that patients across all age groups developed MRSA pericarditis (ranging from 7 months to 75 years). Direct spread from intrathoracic focus of infection (myocardial foci, thoracic surgery or contamination from penetrating trauma), hematogenous spread and extension from subdiaphragmatic suppurative focus are the various mechanisms described for the development of purulent pericarditis.…”
Section: Discussionmentioning
confidence: 93%